1994
DOI: 10.1016/0735-1097(94)90759-5
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of anatomic and electrogram mapping approaches to ablation of the slow pathway of atrioventricular node reentrant tachycardia

Abstract: The anatomic and electrogram mapping approaches for ablation of the slow AV nodal pathway are comparable in efficacy and duration. If the anatomic approach is initially attempted and fails, the electrogram mapping approach may be successful at sites outside the areas targeted in the anatomic approach. With both the anatomic and electrogram mapping approaches, there are significant differences in the atrial electrogram configuration between successful and unsuccessful target sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(68 citation statements)
references
References 8 publications
1
65
1
1
Order By: Relevance
“…8) Hwang, et al have reported successful radiofrequency ablation of the slow pathway in the posterior region of the right atrial septum, 8) as in the present case. 11,12) Furthermore, the slowest of the triple AV nodal pathways and the eccentric retrograde left-sided atrial activation recorded during ventricular pacing disappeared after slow pathway ablation. These results suggest that the eccentric retrograde left-sided pathway forms a part of the slow pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8) Hwang, et al have reported successful radiofrequency ablation of the slow pathway in the posterior region of the right atrial septum, 8) as in the present case. 11,12) Furthermore, the slowest of the triple AV nodal pathways and the eccentric retrograde left-sided atrial activation recorded during ventricular pacing disappeared after slow pathway ablation. These results suggest that the eccentric retrograde left-sided pathway forms a part of the slow pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A steerable 7 Fr ablation catheter with a 4-mm tip electrode (BLAZER-T, model 2531T, EP Technologies, Sunnyvale, CA) was inserted through the right femoral vein to a site near the coronary sinus ostium. Two radiofrequency current deliveries (15 to 25 W, 30 to 40 sec), which were usually used to slow pathway ablation, 10,11) were performed anatomically at the posterior aspect of the tricuspid septal annulus between the coronary sinus ostium and the His bundle recording site (Figure 4). After the selective slow pathway ablation, electrophysiologic study was performed again without isoproterenol infusion.…”
Section: Avnrt With Eccentric Retrograde Activationmentioning
confidence: 99%
“…The incidence of this complication is considered low, with less than 1% in published studies 1,5,[16][17][18] . For that reason, in order to prevent complications such as TAVB during the ablation procedure, it is extremely important to observe the integrity of ventriculoatrial (V-A) conduction or the lengthening of the P-R interval 8,10,19,20 during JET.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of junctional ectopy during perinodal RF energy delivery has been associated with the successful elimination of AVNRT (2). However, the electrophysiological features of different patterns of junctional rhythm (JR) and the importance of the multicomponent atrial electrogram are still unclear.…”
Section: Introductionmentioning
confidence: 99%